Pengaruh Kualitas Produk, Harga, Store Atmosphere, Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di Swalayan Mahkota Gresik (Studi Kasus Pada Konsumen Swalayan Mahkota) - Moh Hafiz Hismuddin; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the effect of Product Quality, Price, Store Atmosphere, Promotion and Service Quality on Purchasing Decisions at Mahkota Gresik Supermarkets. The data used in this study uses primary data by distributing questionnaires to respondents. The study population is consumers who make purchases at the Crown Gresik supermarket. The research sample was taken from the population using a sampling technique in the form of accidental sampling method. The results obtained by using multiple linear regression test Y = 27.120 + 0.399 X1 + 0.434 X2 + 0.230 X3 + 0.428 X4 + 0.684 X5 + e, and the test of this study used the f test and t test. The results of this study indicate that partially Product Quality, Price, Store Atmosphere, Promotion and Service Quality Against Purchasing Decisions at Mahkota Gresik Supermarkets. While simultaneously Product Quality, Price, Store Atmosphere Promotion, and Service Quality Against Purchasing Decisions at Mahkota Gresik Supermarkets.Keywords: Product quality, Pric